Karakteristik Masyarakat Islam Perspektif Al-Qur’an: Analisis QS. Ali-Imran Ayat 110 - Husnul Fikry; Sulaiman W; Nuraini Nuraini; Ainun Mardhiah (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2022)
The Qur’an as a guide has not been understood by some Muslim communities. Therefore, bad behavior still occurs, so the character of Islamic society has a bad impact. This discussion is to reveal